In ovo delivery of various biological supplements, vaccines and drugs in poultry: current knowledge - Saeed, Muhammad; Babazadeh, Daryoush; Naveed, Muhammad; Alagawany, Mahmoud; Abd El‐Hack, Mohamed E; Arain, Muhammad A; Tiwari, Ruchi; Sachan, Swati; Karthik, Kumaragurubaran; Dhama, Kuldeep; Elnesr, Shaaban S; Chao, Sun (Journal of the science of food and agriculture, 2019)
The technique of delivering various nutrients, supplements, immunostimulants, vaccines, and drugs via the in ovo route is gaining wide attention among researchers worldwide for boosting production performance, immunity and safeguarding the health of poultry. It involves direct administration of the nutrients and biologics into poultry eggs during the incubation period and before the chicks hatch out. In ovo delivery of nutrients has been found to be more effective than post‐hatch administration in poultry production. The supplementation of feed additives, nutrients, hormones, probiotics, prebiotics, or their combination via in ovo techniques has shown diverse advantages for poultry products, such as improved growth performance and feed conversion efficiency, optimum development of the gastrointestinal tract, enhancing carcass yield, decreased embryo mortality, and enhanced immunity of poultry. In ovo delivery of vaccination has yielded a better response against various poultry pathogens than vaccination after hatch. So, this review has aimed to provide an insight on in ovo technology and its potential applications in poultry production to deliver different nutrients, supplements, beneficial microbes, vaccines, and drugs directly into the developing embryo to achieve an improvement in post‐hatch growth, immunity, and health of poultry. © 2019 Society of Chemical Industry